2019
DOI: 10.18097/pbmc20196505424
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production by blood immune cells, tumor and its microenvironment, characteristic of extracellular matrix in patients with invasive ductal carcinoma of no special type

Abstract: The aim of this research was to study cytokine production by blood immune cells, tumor, and its microenvironment, and characterize extracellular matrix of patients with invasive ductal carcinoma of no special type and lymphatic metastases. Spontaneous and polyclonal activators stimulated production of cytokines by blood immune cells, tumor and its microenvironment were studied in 95 patients with invasive ductal carcinoma of no special type. The concentration of IL-2, IL-4, IL-6, IL-8, IL-10, IL-17, IL-18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is known that (i) VEGF is a key mediator of angiogenesis in both nominally healthy people and patients with malignant tumors 17 ; (ii) IL-18 creates an immunosuppressive environment for the tumor 18 ; and (iii) TNF-α, GM-CSF, and MCP-1 induce the synthesis of matrix metalloproteinases and activation of epithelial–mesenchymal transition. 11 Therefore, their low spontaneous secretion by the luminal A subtype may be one of the reasons for the relatively slow malignant progression typical for this molecular subtype. 3 , 4 The cultured tumors of the triple-negative molecular subtype featured the highest spontaneous secretion of IL-1β in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that (i) VEGF is a key mediator of angiogenesis in both nominally healthy people and patients with malignant tumors 17 ; (ii) IL-18 creates an immunosuppressive environment for the tumor 18 ; and (iii) TNF-α, GM-CSF, and MCP-1 induce the synthesis of matrix metalloproteinases and activation of epithelial–mesenchymal transition. 11 Therefore, their low spontaneous secretion by the luminal A subtype may be one of the reasons for the relatively slow malignant progression typical for this molecular subtype. 3 , 4 The cultured tumors of the triple-negative molecular subtype featured the highest spontaneous secretion of IL-1β in our study.…”
Section: Resultsmentioning
confidence: 99%
“…2 with PA: 2 μg/mL phytohemagglutinin P, 2 μg/mL phytohemagglutinin M, 4 μg/mL concanavalin A, and 2 μg/mL lipopolysaccharide from E. coli . 11 Vial no. 1 and no.…”
Section: Methodsmentioning
confidence: 99%
“…35,36 It has been reported that lymphocytes can regulate the ECM and endothelial cell function to improve tumor vasculature. 37,38 After sequential fat grafting, the TNFα signaling via NFκB was the most significant down-modulated gene set. We found 3 genes (PAI-1, EDN1, and NFKBIA) from this gene set recognized as hub genes were reduced after sequential fat grafting (eFigure 9B-D in Supplement 1).…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocyte infiltration is a common histologic feature of morphea and is believed to be associated with disease progression . It has been reported that lymphocytes can regulate the ECM and endothelial cell function to improve tumor vasculature . After sequential fat grafting, the TNFα signaling via NFκB was the most significant down-modulated gene set.…”
Section: Discussionmentioning
confidence: 99%
“…The TME components were shown to influence the malignant behaviour of PC [ 8 , 9 , 10 ]. One major impact are cytokines released by both tumour cells directly and by TME components such as cancer-associated fibroblasts (CAFs) and tumour-associated macrophages (TAMs) [ 11 , 12 , 13 ], as they contribute to aggressive cancer progression, metastasis, and suppression of tumour-directed immune surveillance mechanisms [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%